2018
DOI: 10.1111/bph.14136
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin activates single skeletal RyR1 channels but exerts more complex regulation of the cardiac RyR2 isoform

Abstract: Background and PurposeStatins are amongst the most widely prescribed drugs for those at risk of cardiovascular disease, lowering cholesterol levels by inhibiting 3‐hydroxy‐3‐methylglutaryl (HMG)‐CoA reductase. Although effective at preventing cardiovascular disease, statin use is associated with muscle weakness, myopathies and, occasionally, fatal rhabdomyolysis. As simvastatin, a commonly prescribed statin, promotes Ca2+ release from sarcoplasmic reticulum (SR) vesicles, we investigated if simvastatin directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 77 publications
4
22
0
Order By: Relevance
“…In planar lipid bilayers, simvastatin increases the open probability of RyR1 but not RyR2 (28). Similarly, acute application of simvastatin to permeabilized cells shifts the distribution of Ca 2+ spark frequency toward higher values in skeletal fibers (which express predominantly RyR1) but lower values in cardiac myocytes (which express RyR2) (28). Thus, a central role for RyR in statin myopathy fully explains the selectivity of this effect for skeletal over cardiac muscle.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In planar lipid bilayers, simvastatin increases the open probability of RyR1 but not RyR2 (28). Similarly, acute application of simvastatin to permeabilized cells shifts the distribution of Ca 2+ spark frequency toward higher values in skeletal fibers (which express predominantly RyR1) but lower values in cardiac myocytes (which express RyR2) (28). Thus, a central role for RyR in statin myopathy fully explains the selectivity of this effect for skeletal over cardiac muscle.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, direct effects of the statin molecule on RyR might also contribute to selective skeletal myopathy. In planar lipid bilayers, simvastatin increases the open probability of RyR1 but not RyR2 (28). Similarly, acute application of simvastatin to permeabilized cells shifts the distribution of Ca 2+ spark frequency toward higher values in skeletal fibers (which express predominantly RyR1) but lower values in cardiac myocytes (which express RyR2) (28).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Simvastatin is a widely used specific inhibitor of 3-hydroxy-3-methyl-glutaryl-CoA reductase and can reduce the level of low-density lipoprotein cholesterol as well as exert anti-inflammatory effects. [ 20 21 ] A previous clinical study has demonstrated that simvastatin may be associated with visual field stabilization in patients with normal tension glaucoma. A larger scale randomized controlled trial and cost-effective analyses seem to be approved.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies of the isolated ryanodine receptor RyR1 in lipid bilayers recently characterized an interaction with simvastatin which suggested that this drug may facilitate calcium ion leakage [11], a known feature of MHS muscle. Acute exposure to statins in vitro elicits contractures in muscle from MH-susceptible (MHS) pigs but not in muscle from non-susceptible (MHN) animals [12].…”
Section: Introductionmentioning
confidence: 99%